2006
DOI: 10.1021/la061204h
|View full text |Cite
|
Sign up to set email alerts
|

Foaming Properties of Monoglycerol Fatty Acid Esters in Nonpolar Oil Systems

Abstract: Foaming properties of monoglycerol fatty acid esters that have different alkyl chain lengths were studied in different nonpolar oils, namely liquid paraffin (LP 70), squalane, and squalene. The effect of the hydrocarbon chain length of the surfactant, the concentration, the nature of the oil, and the temperature on the nonaqueous foam stability was mainly studied. Five weight percent of glycerol alpha-monododecanoate (monolaurin) formed highly stable foams in squalane at 25 degrees C, and the foams were stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 30 publications
2
55
2
Order By: Relevance
“…Besides, the adsorption behavior of the particles depends on several factors such as structure, size, shape and hydrophobicity. Previously, we have found stable nonaqueous foams from the dispersion of monoglycerides solids in liquid paraffin, squalene, and squalane [38]. Similarly, highly stable nonaqueous foams have been achieved with the solid dispersions in diglyceride/oil systems [39].…”
Section: Introductionmentioning
confidence: 73%
“…Besides, the adsorption behavior of the particles depends on several factors such as structure, size, shape and hydrophobicity. Previously, we have found stable nonaqueous foams from the dispersion of monoglycerides solids in liquid paraffin, squalene, and squalane [38]. Similarly, highly stable nonaqueous foams have been achieved with the solid dispersions in diglyceride/oil systems [39].…”
Section: Introductionmentioning
confidence: 73%
“…When self-assembled structures and particles are blocked inside the foam liquid channels, they can lead to an increase of the foam stability. [22][23][24] Fatty acids are surfactants known to easily produce aqueous foams. 25 The foam stability depends mainly on the size of the self-assembled structures present in the foam liquid channels between the bubbles.…”
mentioning
confidence: 99%
“…This work suggests that the surfactants essentially precipitate at the surface and act as solid stabilizers. Along these lines, Shrestha et al [22][23][24] have shown that fatty acid esters act as surfactants in different non polar and vegetable oil systems, and that the ester particles can stabilize the foam showing higher stability as their concentration is increased. They note that the particle size plays an important role on the stability -smaller sizes are more effective.…”
Section: Specialty Surfactantsmentioning
confidence: 99%
“…In their work, liquid crystals are adsorbed onto the surface and change the rheological properties of the lamellar and foam stability increases with the concentration of crystals. Furthermore, Shrestha et al [23,24] have shown that the stability of non-aqueous foams depends on the surfactant size with smaller sizes producing higher foam stability. Specifically, Friberg and Greene [34] have studied the system triethanolammonium oleate/p-xylene showing that if the concentration of p-xylene is lower than 3% weight, it behaves as lamellar liquid crystals and if it is higher than 13%, the system is an isotropic liquid.…”
Section: Multi-phase Condensed Mediamentioning
confidence: 99%